Interactions between noroviruses, the host, and the microbiota - Walker, Forrest C. (Curr Opin Virol, 2019)
In recent years, appreciation has been growing for the role that the microbiota plays in interactions between the host and various pathogens, including norovirus. Pro- and antiviral effects of the microbiota have been observed for both human and murine noroviruses, and it has become clear that direct effects of microbes and their metabolites as well as indirect effects of commensals on the host are key in modulating pathogenesis. In particular, a common thread has emerged in the ability of members of the microbiota to regulate the host interferon response, thereby modulating norovirus infection. Here we highlight key differences between human and murine noroviruses and their interactions with the microbiota, while also underscoring shared characteristics between noroviruses and other gastrointestinal viruses.